GAMBARAN PENDEKATAN PEMBELAJARAN BIOLOGI KURIKULUM 2013 DI SMA SWASTA SE-KABUPATEN PURWOREJO - ADINUGRAHA, FAJAR; RATNAPURI, ADISTI; PONTO, ANDRIYAN INO; NOVALINA, NOVALINA (Jurnal Ilmu Pendidikan Indonesia, 2021)
The purpose of this study was to determine the description of the Biology learning approach applied in private high schools throughout Purworejo Regency and the factors that support and hinder the learning activities of Biology with the learning approach in private high schools throughout Purworejo Regency. Research methods are surveys and interviews related to the Biology Learning approach conducted in private high schools throughout Purworejo Regency. The research instrument was a non-test instrument and the data obtained were qualitative and quantitative data in the form of Biology National Examination (UN) scores which were analyzed using descriptive statistics. The results obtained are (1). The approach used in Biology Learning in private high schools throughout Purworejo Regency is the Scientific Approach and the Natural Exploration Approach, while the Local Wisdom and Cultural Approach is rarely used. (2). Biology National Examination (UN) scores do not depend on the applied learning approach. This is because the learning outcomes of the Biology UN which are the benchmarks in this study cannot be used as a description of student learning outcomes (cognitive, affective, psychomotor) as a whole. (3). Factors that support and hinder the process of implementing the learning approach are the learning process, motivation, time and the ability of students..